2018
DOI: 10.1111/ajgw.12346
|View full text |Cite
|
Sign up to set email alerts
|

Effect of white wine composition on protein haze potential

Abstract: Background and Aims Haze formation in white wine is caused by protein aggregation and can be influenced by many other wine components. This study investigated the impact of wine matrix composition on haze formation in 60 white wines to assess the feasibility of predicting haze by measuring selected wine components. Methods and Results Sixteen wine matrix components previously shown to influence wine haze in model and reconstitution studies were analysed in a range of white wines and compared to the amount of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…A key difference, however, between the semi-commercial and pilot scale UF treatments was that permeate was not heat stable; ΔNTU was 3.8 and almost 10 mg/L of haze-forming protein was detected in the permeate. The concentration of haze-forming proteins alone is not considered a reliable indicator of haze potential (McRae et al 2018b) and this was supported by haze potential and protein data for retentate and permeate in the current study. The retentate protein concentration was 8.6 times higher than that of the SB wine, yet the corresponding haze potential was only 5.4 times higher.…”
Section: Bentonite Fining Of Retentate From Pilot Scale Uf Of Sbs Andsupporting
confidence: 69%
See 3 more Smart Citations
“…A key difference, however, between the semi-commercial and pilot scale UF treatments was that permeate was not heat stable; ΔNTU was 3.8 and almost 10 mg/L of haze-forming protein was detected in the permeate. The concentration of haze-forming proteins alone is not considered a reliable indicator of haze potential (McRae et al 2018b) and this was supported by haze potential and protein data for retentate and permeate in the current study. The retentate protein concentration was 8.6 times higher than that of the SB wine, yet the corresponding haze potential was only 5.4 times higher.…”
Section: Bentonite Fining Of Retentate From Pilot Scale Uf Of Sbs Andsupporting
confidence: 69%
“…The conductivity of Mar was 25 and 32% higher than that of SBS and SB wines, respectively (data not shown), which further explains why protein was more readily removed from the Mar retentate; that is increased ionic strength facilitated protein aggregation in a previous study (Marangon et al 2011). Certainly, it has been established that wine protein aggregation and haze formation is a multifactorial process (McRae et al 2018b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study on Chilean Sauvignon Blanc wine reported that more protein haze formation in wine was observed by increasing the electrical conductivity [78]. However, a more recent study on a range of Australian white wines showed a negative correlation between protein haze formation and electrical conductivity [79]. These contradictory results could be related to the differences in other wine components of importance to protein haze formation.…”
Section: Ion Concentration and Electrical Conductivitymentioning
confidence: 95%